Urgensi Pembentukan Tindak Pidana Khusus Cyberbullying dalam Perspektif Kebebasan Berekspresi di Indonesia - I Made Dwi Cahya Prayogi Putra; Made Sugi Hartono; I Wayan Kertih (Perspektif Administrasi Publik dan hukum, 2026)
The rapid expansion of digital media use has intensified the practice of cyberbullying as a form of non-physical violence that seriously affects victims’ mental health, dignity, and human rights. In Indonesia, cyberbullying is not specifically regulated and still relies on general provisions in the Law on Electronic Information and Transactions (EIT Law), which often lead to multiple interpretations, overcriminalization, and potential restrictions on freedom of expression. This article aims to analyze the urgency of establishing a specific criminal offense for cyberbullying within the framework of human rights protection and the principle of proportionality in limiting freedom of expression in the digital sphere. This study employs a normative legal research method using statutory, conceptual, and comparative approaches to regulations in several countries. The findings indicate that the absence of specific norms on cyberbullying creates legal uncertainty and weakens victim protection while also opening opportunities for the misuse of legal provisions against legitimate expression. Therefore, it is necessary to formulate clear, proportional, and victim-oriented criminal regulations, supported by fair and transparent law enforcement mechanisms that are consistent with human rights principles in the digital era.